Augmented Reality Advertising in Entertainment Programming: An Exploration Across Cultures. (March 2023) - Lin, Hui-Fei; Tsai, Hsin-yi Sandy; Yeo, Benjamin
Augmented reality (AR) ads in entertainment programming are fairly new and not extensively studied. Given the lack of precedence, this exploratory study applies the Limited-Capacity Model and Schema Congruity Theory (SCT) to examine their advertising effects. We used a 2 (type of product placement: title sponsorship placement vs. background placement) × 2 (congruence with the characteristics of the programme: congruent vs. incongruent) × 2 (cross-screen advertising: 3D dynamic advertisement vs. 2D advertisement) × 2 (culture: United States vs. Taiwan) between-subjects experiment design. Our results show incongruent brand recall is greater than congruent recall for American viewers and Taiwanese viewers have better attitudes towards AR dynamic advertisement presentations of title sponsorships that are congruent with the programme. Global AR advertising campaigns can benefit from cultural differences. We propose three specific recommendations to advertisers seeking to apply AR in product placements: (a) For American viewers, incongruous product placements should be able to facilitate positive advertisement attitudes, (b) In TV shows, 2D advertisements can improve advertisement attitudes in some cases, and (c) For Taiwanese audiences, congruent title sponsorships or incongruent background placements can produce better advertisement attitudes.